Renal safety profile of di-peptidyl-peptidase inhibitors: a review of available literature - Dey, Arindam; A.G., Unnikrishanan; Saxena, Gaurav; Jain, Rishi (International Journal of Basic & Clinical Pharmacology, 2017)
Diabetic Nephropathy has become the single most import cause of End Stage Renal Disease (ESRD). Various strategies to limit or slow the progress the Diabetic nephropathy are suggested by the guidelines and evidences. By maintaining strict glycemic control the progression of diabetic nephropathy can be altered. Glycemic control in diabetic patients with nephropathy is complex as falling eGFR renders many ant diabetic medications contraindicated while others are needed to be done in low dose. The intent of this review article is to collate the available evidences for renal safety with one such anti diabetic class of medication, dipeptidyl peptidase 4 inhibitor and evaluate the guideline based antidiabetic treatment in Type 2 Diabetes Mellitus patients with renal insufficiency.